PROFIL BERPIKIR KRITIS SISWA KELAS IX SMP NEGERI 1 TOMINI DALAM MEMECAHKAN MASALAH PADA MATERI PERSAMAAN GARIS LURUS - Lilis Lilis; Sutji Rochaminah; Muh. Hasbi (Universitas Tadulako, 2025)
This study aims to describe the critical thinking of class students. IX SMP Negeri 1 Tomini in sloving problems on the material of linear equations straight. The subject in this study were 3 students of class IX A of SMP Negeri 1 Tomini which has a category of students with high mathematical abilities, students with moderate mathematical abilities, and students mathematical abilities lo. This type of research is descriptive research with a quantitative approach, qualitative. This research instrument consists of the main instrument, namely the researcher it self in the supporting instruments in this research are writtten test and interview. The results of this study indicate that DTA and RM completed straight line equation questions by fulfilling all critical thingking criteria starting from the focus, reason, inference, situation, clarity and overview indicator, but DTA and RM have different thingking activities, namely DTA or subject have higt mathematical abilities in completing tasks with solutions which is longer with careful though. While RM or subject low mathematical ability in completing task with solutions in a more concise manner. This is supported by answer data written and interview. While T or subject with mathematical abilities low in completing the task in a very short way, but T fulfilles 5 critical thingking criteria starting from the focus, reason, situation, clarity, and overview indicators. But T does not meet one indicator, namely inference because T cannot conclude the final answer.